Evaluating Security Performance Forecasts - Neave, Edwin H.; Wiginton, John C. (Management Science, 1976)
The value of information is used to evaluate the worth of a forecast to the recipient. The basic concepts of information economics are augmented by modern Bayesian statistical methods to provide a means of learning about the true, but unknown, information structure and distribution of state probabilities. The value of information measure appears in this context to be useful in detecting temporal changes in the information structure, in a fashion somewhat analogous to the use of control limits.